„Nie wiedziałem wtedy...” O dwóch wierszach autotematycznych - Pasterski, Janusz (Tematy i Konteksty, 2018)
The author discusses the autothematic motifs in the poems Sitowie of Julian Tuwim and Przeciwne wiatry of Tomasz Różycki. The author analyses both poems and compares the transformations of the autothematic motifs, emphasizing the connections with literary tradition and the dialogue of artistic poets’ attitudes. In both litterary works the key problem is the relation between words and things.